Compressive behaviour and modelling of CFRP-confined ultra-high performance concrete under cyclic loads. (6th December 2021) - Huang, Liang; Xie, Jianhe; Li, Liming; Xu, Baoqin; Huang, Peiyan; Lu, Zhongyu
Highlights: The cyclic compressive behaviour of CFRP-confined UHPC was investigated for the first time. A modified cyclic strain–stress model was proposed. The stress–strain behaviour of CFRP-confined UHPC was compared to CFRP-confined NSC. The strain–stress behaviours of confined UHPC under monotonic loading and cyclic loading were compared. The effect of the cyclic-loading mode on the CFRP confinement was examined. Abstract: The application of fibre-reinforced polymer (FRP) composites to enhance the strength and deformability of confined concrete has attracted increasing interest. However, the confinement demand of concrete increases proportionally with its strength, resulting in higher confinement requirements for ultra-high performance concrete (UHPC). This paper presents an experimental study that investigated the compressive behaviour of confined UHPC with carbon FRP sheets under cyclic axial compression. A modelling study on the cyclic stress–strain response of FRP-confined UHPC was also performed. The influences of the confinement ratio and cyclic-loading mode on the stress–strain curve, plastic strain, stress deterioration ratio and secant modulus were analysed. The findings for the stress–strain behaviour of FRP-confined UHPC were compared to those of conventional concrete confined with FRP. Based on the interpretation of the test results from this study and a comprehensive assessment of cyclic stress–strain models developed for FRP-confined conventional concrete, a stress–strain model for FRP-confined UHPC under cyclic axial compression was proposed. The results show that the proposed model reasonably predicts the stress–strain responses of FRP-confined UHPC.